Global leadership in a university setting - Hassanzadeh, Maryam; Silong, Abu Daud; Hossein Zadeh, Ali Mohammad; Ghadirian, Hajar; Kasmaienezhadfard, Sara (Mediterranean Center of Social and Educational Research, 2016)
What is global leadership? How can we develop global leadership for a university? This study was conducted using the qualitative approach through in-depth interviews of eight selected top leaders in a selected university. Based on the in-depth interviews, the findings discussed are as follows; Global leadership is related to diversity. Global leaders need to be developed with additional competencies to lead a university and to be able to compete worldwide. Global leadership has to operate in diverse situations. This means that a global leader has to understand different cultures, different ideas and different beliefs. So a global leader has to understand leading in diversity, which requires a different set of competencies. These include attitudes, skills and knowledge. This study is significant because it fills a gap in current knowledge regarding the experience that leaders perceived to be important in understanding and developing global leadership.